The effect of Heyzine flipbook-based digital learning media on students' understanding of mathematical concepts - Mawaddah, Dina; Gusmania, Yesi; Ismarti, Ismarti (Universitas Riau Kepulauan, 2025)
Based on a preliminary survey, students at Grade X SMK IT Darussalam Boarding School 01 Batam demonstrated a low understanding of mathematical concepts. This study aimed to examine: (1) the effect of Heyzine Flipbook-based digital learning media on students’ mathematical concept understanding, (2) the effect of conventional learning, and (3) the differences between the two methods. Using a quantitative approach, the population included all Grade X students in the 2025/2026 academic year. Purposive sampling was applied, with Grade X TKJ A (24 students) as the experimental class and Grade X TKJ B (19 students) as the control class. Data were collected through essay tests, consisting of three validated and reliable items. Data analysis involved assessing normality and homogeneity, as well as conducting hypothesis tests. The results revealed that: (1) Heyzine Flipbook significantly improved students’ understanding of mathematical concepts, (2) conventional learning also showed an effect on students’ understanding, though at a lower level, and (3) a significant difference was found between the two approaches, with Heyzine Flipbook proving more effective in enhancing students’ mathematical concept understanding.